Crop Livestock System in South Sulawesi: Review of Implementary Activities - Ella, Andi (Indonesian Animal Sciences Society, 2002)
South Sulawesi has considerated having amount of rice field i.e. 598,218 hectare about 21.49% out of the total land for agriculture activities. Some of these are irrigated rice field, either technical or non-technical irrigated which contributes to the production of rice. These land is also used as production center for cattle. The population of cattle is 805,868 heads in 1995 decreased to 749,327 heads in 1999 (1.8% decreased each year). Both commodities (rice and cattle) were agribusiness oriented. However, the productivity of rice has been facing leveling off, with the maximum average is 4 â 6 ton/ha. It is likely that the due to phenomena degradation of the soil, so that it can not support the optimum condition of the growing rice because of inadequate a certain nutrient or lack of organic carbon which can not support the uptake of a certain nutrient. One of the alternative to improve these condition was the application of compost which produced from cattle manure. The main feed of cattle can be provided from rice straw, which is available with the amount of 4-5 ton/ha/growing season. It means that the potential production of rice straw every season was 1,196,432 heaps, which can be used as cattle, feed to increase cattle production. Each cattle could produce 4 â 5 ton fresh manure/year, which can be processed to cattle manure (compost) at the rate of 2 ton/year/cattle, so that it is estimated the number of compost can be produced in South Sulawesi was 1,498,654 ton/year. This can be applied to 749,327 ha of rice field with the rate of 1.5 â 2 t/ha. Therefore, the integration of cattle into a rice system could increased productivity of the two commodities. The implementation of CLS in South Sulawesi has the following problems: a) in the intensive area of growing rice, the threshing mashed was done using power thresher, and cutting the rice straw at the top (one third from the top) which cause problem for farmers to collect the rice straw for cattle feed, b) most of farmers have no any experience in using rice straw for fodder, c) the majority of farmers do not have animal shelter. Â Key words: Integration, feed cattle, rice straw, fermentation